An International Study of Management Perceptions of the Working Capital Process - Gentry, James A.; Mehta, Dileep R.; Bhattacharyya, S. K.; Cobbaut, Robert; Scaringella, Jean-louis (Journal of International Business Studies, 1979)
Working capital literature is rather limited and the process of managing short‐term resources is not understood well by academicians. In contrast, corporate managers are continuously involved in the working capital decision-making process, but their perspective is limited to the practices within their firm. In order to fill this gap in the working capital literature, a study of management perceptions of the working capital process was undertaken. A survey was used to collect the information from the sample of marketing, production, and financial executives in large corporations in Belgium, France, India, and the United States. The study intercepts management ranking of working capital objectives and indicates the need to improve finacial planning models to include explicitly short–run objectives; further, predictability of cash inflows and outflows is examined and the potential factors affecting the predictability are evaluated. Finally, this study examines management perceptions of long-range objectives in order to provide a proper perspective to the short-run financial planning.